A solitary fibrous tumor in the pelvic cavity of a patient with Doege-Potter syndrome: a case report - Yukiko Wada; Keiichi Okano; Yasuhisa Ando; Jun Uemura; Hironobu Suto; Eisuke Asano; Takayoshi Kishino; Minoru Oshima; Kensuke Kumamoto; Hisashi Usuki; Yasuyuki Suzuki (Surgical Case Reports, 2019)
Abstract Background A solitary fibrous tumor (SFT) is a mesenchymal lesion, which commonly develops in the thorax. Non-islet cell hypoglycemia is a rare paraneoplastic phenomenon caused by an extra-pancreatic tumor. We report a rare case of a pelvic SFT with severe hypoglycemia, which was considered to be Doege-Potter syndrome. Case presentation A 72-year-old man was referred to our hospital for treatment of hypoglycemia and a large pelvic tumor. His blood glucose level was 52 mg/dl; serum insulin level, 1.0 μIU/ml; C-peptide level, 0.2 ng/ml; and insulin-like growth factor-I (IGF-I) level, 31 ng/ml. Contrast-enhanced computed tomography (CT) showed a 13-cm mass in the pelvic cavity. Magnetic resonance imaging (MRI) revealed a lobulated tumor with iso- and high-intensity areas combined in T2-weighted images. No clear invasion to any adjacent organs was identified. The tumor was resected, and hypoglycemic symptoms disappeared immediately. Pathological diagnosis was an SFT with malignant potential that secreted IGF-II and caused hypoglycemia. There has been no tumor recurrence during the 1 year of follow-up. Conclusion Non-islet cell tumor hypoglycemia should be considered in the differential diagnosis of patients presenting with tumors and hypoglycemia.